STRATEGI PENINGKATAN LIFE SKILL PESERTA DIDIK PKBM RINI HANDAYANI BEKASI MELALUI PELATIHAN DESAIN GRAFIS - Royyan, Mochammad Habib; Santika, Tika; Muis, Abdul (IKIP Siliwangi, 2025)
This research aims to improve the life skills of learners at PKBM Rini Handayani Bekasi through graphic design training. Using a descriptive qualitative approach, this study examines the strategies used to improve these skills, which include personal, social, academic, and vocational skills. Data were obtained from respondents consisting of trainees, head of the institution, and instructors. The results show that graphic design training contributes positively to the development of technical and social skills, which can improve learners' work readiness. This study emphasizes the importance of a structured strategy in non-formal training to improve competitiveness in the job market.